Memory Reconfiguration in Post-War Taiwanese Literature - Yu, Chung-Yen. author. aut Link
X, 128 p.
Keywords: This book examines the impact of martial law on transgenerational memory in post-World War II Taiwan. Through an intense focus on the symptoms of memories, Yu argues that collective remembrances in post-war Taiwan must be studied alongside the islanders' collective amnesia, as the post-war regime coerced its citizens into forgetting. To do so, the book examines the core issue through the lens of two fictional works: Green Island (2016) by Shawna Yang Ryan and The Stolen Bicycle (originally published in 2015, translated in 2017) by Ming-yi Wu, whose narrators belong to the post-war generation and find themselves unable to understand their parents' traumas. It also observes how the war generation memorize consecutive and entangled colonial experiences, experiencing linguistic and social diaspora without the act of migration. Ultimately, Yu argues that post-memory in these circumstances not only refers to secondary memory but bears an anti-memory characteristic as Taiwanese society under martial law shunned the traumas of WWII and the March Massacre in 1947. Chung-Yen Yu received his PhD from Australian National University. .